The Level of Climate Change Awareness among Citizens of Bitung City, Indonesia - Syamsudin Nggole; Wido Prananing Tyas; Wisnu Pradoto (Jurnal Wilayah dan Lingkungan, 2019)
Knowledge about citizen’s climate change awareness level is needed to establish an appropriate policy to cope with climate change hazard, particularly in a highly vulnerable country like Indonesia. However, research regarding climate change awareness among citizens in Indonesian cities is limited. This research aims to investigate the level of climate change awareness among the citizens in Bitung City, a medium-sized city in the eastern part of Indonesia. The survey method is used in the research by analyzing questionnaires collected from the citizens. Three variables for measuring the awareness level include public concerns on climate variability, the causes of climate change, and the impacts of climate change. The findings show that the citizens of Bitung have a ”quite strong” awareness level. This contributes to the recognition of citizens’ characteristics toward climate change useful to climate change policy formulation in Indonesia, particularly the Bitung City Government. Some recommendations for the government include the incorporation of climate change issue to the citizens’ daily life and development programs by establishing a special task force of climate change at the city level.